PERIPHRASTIC CAUSATIVE CONSTRUCTIONS IN THE PUNAN DAYAK LANGUAGE - Muhammad Thobroni; Romadhan, Achmad Dicky; Alien Kurnia Warya Selia (LEMBAGA PENELITIAN DAN PENGABDIAN PADA MASYARAKAT, 2025)
The Punan Dayak language is one of the regional languages in the province of North Kalimantan. The Punan Dayak language is widely used by the Punan Dayak tribe in Malinau Regency. The Punan Dayak language is part of the Austronesian language family. This study discusses analytical or periphrastic causatives in the Punan Dayak language. This study attempts to reveal the form of analytical causatives in the Dayak Punan language, including the verbs that mark these constructions. The data collection methods used in this study were observation and interviews. The research data were taken from direct speech by Dayak Punan speakers. The informants in this study were from the Dayak Punan tribe, aged between 25 and 55 years. The data analysis method used in this study was the distribution technique. Based on the results of this study, there are two types of verbs that are the main predicates in analytical causative constructions in the Dayak Punan language. These verbs are nucuh and menah. The distribution of these two verbs is different. The verb nucuh can appear in analytical or periphrastic causative constructions that have embedded clauses with transitive and intransitive verbs as predicates. On the other hand, the verb menah can only appear in analytical or periphrastic causative constructions that have an embedded clause with an intransitive verb predicate. The implications of this research are expected to become a means of preserving the Dayak Punan language and a basis for compiling Dayak Punan grammar.